Detection of somaclonal variation by random amplified polymorphic DNA analysis during micropropagation of Phalaenopsis bellina (Rchb.f.) Christenson - Khoddamzadeh, Amir Ali; Sinniah, Uma Rani; Abdul Kadir, Mihdzar; Kadzimin, Saleh; Mahmood, Maziah; Subramaniam, Sreeramanan (Academic Journals, 2010)
Phalaenopsis bellina (Rchb.f.) Christenson orchid species are known for their beautiful flower shape, graceful inflorescence and fragrance. Protocorm-like bodies (PLBs) of P. bellina were induced from leaf segments. The PLBs were then subjected to proliferation using ½ strength Murashige and Skoog (MS) media with two subcultures at three months intervals. Twelve decamer random amplified polymorphic DNA (RAPD) primers were used to study somaclonal variation among the mother plant, the initially induced PLBs and proliferated PLBs after 3 and 6 months in culture. Eight out of twelve primers produced 172 bands with 18 polymorphic bands in all the treatments. The amplified products varied between 125 to 8000 bp. Among the primers used, P 16 produced the highest number of bands (29), while primer OPU 10 produced the lowest number (15). The range of similarity coefficient was from 0.83 to 1.0 among the different sub-cultures and mother plant (MP). It was found that minimal or no changes occurred between the MP and the PLBs produced after 3 months of induction. The induced PLBs were then subcultured for six months for proliferation and this resulted in about 17% dissimilarity with MP. It is reported that micropropagation of P. bellina can be carried out successfully using ½ strength MS media for 6 months but further proliferation may result in somaclonal variation which might change the prolific characteristic of this orchids.